Abscisic acid biosynthesis, metabolism and signaling in ripening fruit - Wu, Wei; Cao, Shi-feng; Shi, Li-yu; Chen, Wei; Yin, Xue-ren; Yang, Zhen-feng (Frontiers in Plant Science, 2023)
Fruits are highly recommended nowadays in human diets because they are rich in vitamins, minerals, fibers and other necessary nutrients. The final stage of fruit production, known as ripening, plays a crucial role in determining the fruit’s quality and commercial value. This is a complex physiological process, which involves many phytohormones and regulatory factors. Among the phytohormones involved in fruit ripening, abscisic acid (ABA) holds significant importance. ABA levels generally increase during the ripening process in most fruits, and applying ABA externally can enhance fruit flavor, hasten softening, and promote color development through complex signal regulation. Therefore, gaining a deeper understanding of ABA’s mechanisms in fruit ripening is valuable for regulating various fruit characteristics, making them more suitable for consumption or storage. This, in turn, can generate greater economic benefits and reduce postharvest losses. This article provides an overview of the relationship between ABA and fruit ripening. It summarizes the effects of ABA on ripening related traits, covering the biochemical aspects and the underlying molecular mechanisms. Additionally, the article discusses the interactions of ABA with other phytohormones during fruit ripening, especially ethylene, and provides perspectives for future exploration in this field.